2020
DOI: 10.3748/wjg.v26.i26.3750
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived mesenchymal stem cells alleviate TNBS-induced colitis in rats by influencing intestinal epithelial cell regeneration, Wnt signaling, and T cell immunity

Abstract: BACKGROUND Conventional Crohn’s disease (CD) treatments are supportive rather than curative and have serious side effects. Adipose-derived mesenchymal stem cells (ADSCs) have been gradually applied to treat various diseases. The therapeutic effect and underlying mechanism of ADSCs on CD are still not clear. AIM To investigate the effect of ADSC administration on CD and explore the potential mechanisms. METHODS Wistar rats were administered wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Likewise, other examinations indicated that AT-MSC administration attenuated the disease activity index (DAI) and improved the severity of colitis in a rodent CD model. Significantly, regulation of intestinal epithelial cell (IEC) proliferation, Wnt signaling pathway, and T cell immunity were suggested as the underlying mechanism of the AT-MSC-prompted therapeutic effect in the rodent CD model [ 111 ]. The crucial role of the Wnt axis has already been confirmed in murine IBD, where Roger et al showed that injection of a Wnt agonist to STAT6 (−/−) mice induced the Wnt signaling in the damaged mucosa and accelerated wound-healing in the TNBS-induced CD model [ 112 ].…”
Section: Application Of Msc Therapy In Immune-mediated Disordersmentioning
confidence: 99%
“…Likewise, other examinations indicated that AT-MSC administration attenuated the disease activity index (DAI) and improved the severity of colitis in a rodent CD model. Significantly, regulation of intestinal epithelial cell (IEC) proliferation, Wnt signaling pathway, and T cell immunity were suggested as the underlying mechanism of the AT-MSC-prompted therapeutic effect in the rodent CD model [ 111 ]. The crucial role of the Wnt axis has already been confirmed in murine IBD, where Roger et al showed that injection of a Wnt agonist to STAT6 (−/−) mice induced the Wnt signaling in the damaged mucosa and accelerated wound-healing in the TNBS-induced CD model [ 112 ].…”
Section: Application Of Msc Therapy In Immune-mediated Disordersmentioning
confidence: 99%
“…Of the 28 studies, 12 [ 16 , 18 23 , 25 , 27 , 28 , 31 , 32 ] reported DAI scores, 9 on day 1 ( n = 118 animals), 9 on day 3 ( n = 118), 11 on day 5 ( n = 134), 3 on day 7 ( n = 124), and 5 on day 9 ( n = 64). A random effects model was chosen for analysis, and the Cohen method was used to assess differences in DAI between the treatment and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneity exhibited by the day 3 and 9 subgroups fell to moderate levels after deleting the studies of Banerjee et al [ 23 ] and Gonzalez-Rey et al [ 21 ]; and Gonzalez-Rey et al [ 21 ], respectively. The heterogeneity associated with the day 1 and 7 subgroup disappeared after excluding Kawata et al [ 32 ] and Forte et al [ 16 ]; Gao et al [ 18 ], Gonzalez-Rey et al [ 21 ] and Ji Young Lim et al [ 26 ], respectively.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These EVs have the ability to migrate into damaged tissues, promote tissue repair, and modulate immune responses. 20 , 129 , 131 Therefore, EVs may serve as potential nanocarriers for efficient, targeted drug delivery in IBD treatment.…”
Section: Nano-mediated Therapiesmentioning
confidence: 99%